ICONOGRAPHY OF THE CASULLA DE LAS PALMERAS (CHASUBLE OF PALM TREES), A 16TH-CENTURY CHASUBLE OF THE CATHEDRAL BASILICA OF LIMA - Victorio Cánovas, Emma Patricia (2013)
The liturgical ornaments corresponding to the 16th century are not many. However,in the collection belonging to the Cathedral of Lima there are some pieces ofthis period which are of European origin. A chasuble which has been identifiedas the Casulla de las Palmeras outstands among them because of its iconographicmotifs. This article deals about it.